From "Los Serrano" to "CSI" (Journal of Parents and Teachers, 2014)
Today, television programmes are no longer designed for women in the morning and for families at night. Instead, they must now modify their programming and adapt it to reach the widest possible audience.One of the television channels that has achieved this objective is Telecinco con los Serrano; a series that takes place in a house, a bar and a school and deals with current affairs issues such as love, jealousy, economic problems, etc. Another very successful series is "Yo soy Bea" inspired by the Antena 3 series "Yo soy Betty, la fea"; this series tells the story of a young woman who has two brakes in her life: her poor physical attractiveness and the absence of social skills.House is another series that heads the success rankings, in which the viewer is brought closer to the world of medicine by the main character, Dr. House, who treats patients with little-known ailments with the help of a select group of skilled assistants.
Keywords: media; television; TV programmes